CRANIAL SIZE VARIATION AND LINEAGE DIVERSITY IN EARLY PLEISTOCENE HOMO. (1st March 2014) - Scott, Jeremiah E.
Abstract: A recent article in this journal concluded that a sample of early Pleistocene hominin crania assigned to genus Homo exhibits a pattern of size variation that is time dependent, with specimens from different time periods being more different from each other, on average, than are specimens from the same time period. The authors of this study argued that such a pattern is not consistent with the presence of multiple lineages within the sample, but rather supports the hypothesis that the fossils represent an anagenetically evolving lineage (i.e., an evolutionary species). However, the multiple‐lineage models considered in that study do not reflect the multiple‐species alternatives that have been proposed for early Pleistocene Homo . Using simulated data sets, I show that fossil assemblages that contain multiple lineages can exhibit the time‐dependent pattern of variation specified for the single‐lineage model under certain conditions, particularly when temporal overlap among fossil specimens attributed to the lineages is limited. These results do not reject the single‐lineage hypothesis, but they do indicate that rejection of multiple lineages in the early Pleistocene Homo fossil record is premature, and that other sources of variation, such as differences in cranial shape, should be considered.